Analysis of environmental factors of enterprise at the regional market of oil products - M. Khasheva, Zarema (2019)
Forming of the strategic management system, including development management instruments strategy and taking into account the features of branch markets, reports a necessary effective operating of enterprise of the real sector of economy condition. The research results of the use of state statistics data of factors of environmental enterprise of “TAT-OIL- PRODUCT” are presented in the paper. indirect and direct influences are distinguished in a number of factors. In the composition, indirect influences of macromedias-political, economic, sociocultural and technological factors are analyzed. In this composition, the factors of direct influence the factors of microenvironment-consumers and competitors are distinguished. According to the analysis of environmental factors, the thesis reports that the necessary and independent stage of forming the development strategy of enterprise is reasonable. Distinctive features related to the specific activity of enterprises at the regional market of oil products can show the organizational strategic goals and tasks presented in the paper: increase of volume of wholesale and retail circulation, optimization of stock-in-trades on storages, improvement of quality of maintenance of customers, optimization of logistic processes, development of assortment politics, etc. The special attention is paid to the regional market of oil and oil products, on which the normatively-legal pre-conditions are formed for a competition between the analysis of apeak-integrated petroleum companies. Analysis of dynamics of financially-economic activity of enterprise at the regional market of oil products allowed to deduce the reasons of worsening of the indices including the low level of efficiency of strategic analysis of enterprise’s environmental factors; the absence of a skilled specialists in the area of strategic management, effectively capable of using modern software products based on the system of the balanced indices.